Applying Smart Breathing as A Community Response and Promotional Method to Avoid Respiratory Disorders : Penerapan Napas Cerdas Sebagai Strategi Promotif dan Tanggap Komunitas dalam Pencegahan Gangguan Pernapasan - Ulfa Nur Rohmah; Antarini Idriansari; Safa Tiara Kiani; Lisa Rizky Amalia; Dhona Andhini (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Disorders of the respiratory system continue to be a serious health issue that affects people's quality of life. Unhealthy environmental conditions, significant exposure to pollution, and poor practices of clean and healthy living habits raise the risk of respiratory disorders. The purpose of this activity is to develop community awareness and ability in avoiding respiratory illnesses using the Smart Breathing program as a community promotion and responsive strategy. The activity is carried out through the steps of planning, implementation, assessment, and follow-up. Program execution comprises lung health education, demonstrations of daily activity-based breathing exercises, the construction of local educational media (posters and respiratory kit), and a proclamation of community commitment. 55 participants were evaluated utilizing pretests and posttests. The results demonstrated an increase in community knowledge, with an average pretest score of 53.22 and a posttest score of 73.23. These findings indicate that the Smart Breathing program is effective in increasing community understanding of respiratory disorder prevention, thus contributing to strengthening health awareness, improving self-management skills, and encouraging preventive behaviors in preventing respiratory disorders.